2004
DOI: 10.1007/s11881-004-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparing novice teachers to develop basic reading and spelling skills in children

Abstract: This study examined the word-structure knowledge of novice teachers and the progress of children tutored by a subgroup of the teachers. Teachers' word-structure knowledge was assessed using three tasks: graphophonemic segmentation, classification of pseudowords by syllable type, and classification of real words as phonetically regular or irregular. Tutored children were assessed on several measures of basic reading and spelling skills. Novice teachers who received word-structure instruction outperformed a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
104
3
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 21 publications
10
104
3
4
Order By: Relevance
“…In our review, several studies of reading and mathematics revealed teacher educator approaches to integrating how to teach content with the procedural knowledge necessary for implementing instruction and knowledge of student performance (Alexander, Lignugaris-Kraft, & Forbush, 2007;Paulsen, 2005;Spear-Swerling, 2009;Spear-Swerling & Brucker, 2004). Mostly, these approaches involved contentfocused methods coursework combined with highly structured field experiences.…”
Section: Pedagogical Content Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…In our review, several studies of reading and mathematics revealed teacher educator approaches to integrating how to teach content with the procedural knowledge necessary for implementing instruction and knowledge of student performance (Alexander, Lignugaris-Kraft, & Forbush, 2007;Paulsen, 2005;Spear-Swerling, 2009;Spear-Swerling & Brucker, 2004). Mostly, these approaches involved contentfocused methods coursework combined with highly structured field experiences.…”
Section: Pedagogical Content Knowledgementioning
confidence: 99%
“…Similarly, in the area of reading, researchers have demonstrated that carefully designed coursework accompanied by structured field experiences enabled preservice teachers, both those with and without prior teaching experience, to grow in their content knowledge for teaching reading and in their ability to promote student reading achievement (SpearSwerling, 2009;Spear-Swerling & Brucker, 2004). In the e studies, preservice special education teachers enrolled in a language arts course in which they learned about reading development, struggles that students encounter, English word structure, phonics, and reading assessments.…”
Section: Pedagogical Content Knowledgementioning
confidence: 99%
“…These studies reiterate the need to strengthen teachers' disciplinary knowledge of spoken and written language structures. This call to increase teacher knowledge is bolstered by a growing body of research that has revealed significant links between teacher knowledge and practice, and most importantly, student reading achievement (Foorman & Moats, 2004;McCutchen, Abbott et al, 2002;Spear-Swerling & Brucker, 2004). The results of these studies demonstrate that educators who have knowledge of phonological awareness and the alphabetic principle, and understand how to apply such knowledge in classrooms, can positively affect student outcomes (Bos et al, 1999;McCutchen & Berninger, 1999;O'Connor, 1999).…”
mentioning
confidence: 99%
“…This idea is highly stressed by many educators such as Block and Israel (2005), Bos, Mather, Narr, and Babur (1999), Darling-Hammond (2000), Harries and Sass (2008), Snow (2002), Spear-Swerling and Brucker (2004).…”
Section: Discussion Of the Results Of The Second Questionmentioning
confidence: 99%